Nemaspela ladae sp. n., a new troglobitic nemastomatid (Opiliones, Dyspnoi, Nemastomatidae) from a Dinaric cave - Karaman, Ivo M. (Zootaxa, 2013)
A new troglobitic Nemastomatidae from Mt. Romanija in Bosnia, is described and provisionally placed in the otherwise Caucasian genus Nemaspela Šilhavý, 1966 for sharing morphological similarities. Nemaspela ladae sp. n. seems not closely related to the second troglobitic Balkan genus Hadzinia Šilhavý, 1966, which shows closer relationship with Nemaspela femorecurvata Martens, 2006. New male specific characters shared by Hadzinia karamani (Hadži, 1940) and several similar, still undescribed species, indicate Hadzinia as an independent lineage. The unusual distribution of the Hadzinia-Nemaspela complex might indicate its relictual status as elements of the paleo-European mainland fauna, which survived adverse climatic changes during the Pleistocene in southern refuges. Possible relation of this complex with the fossils Mitostoma gruberi Dunlop and Mitov, 2009 from Bitterfeld and Baltic ambers is discussed. Further studies of the entire Hadzinia-Nemaspela complex and relatives are necessary to solve their phyletic and unusual zoogeographic connections.